2022
DOI: 10.1088/1361-6668/ac93bd
|View full text |Cite
|
Sign up to set email alerts
|

Coupling electromagnetic numerical models of HTS coils to electrical circuits: multi-scale and homogeneous methodologies using the T-A formulation

Abstract: Numerical simulation is an effective tool for predicting the electromagnetic behavior of superconductors. Recently, a finite element method (FEM)-based model coupling the T-A formulation with an electrical circuit has been proposed: the model presents the superconducting constituent as a global voltage parameter in the electrical circuit. This allows assessing the overall behavior of complex high-temperature superconductor (HTS) systems involving multiple power items, while keeping a high degree of precision o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The inductance value at the initial time is about 94% of the normal inductance. This value is basically consistent with the 90% obtained in the literature [21]. When the excitation current is stabilized at the operating current, the inductance still keeps increasing with a lower growth rate than in the excited phase.…”
Section: Effect Of Excitation Speed On the Inductance Of Hts Coilsupporting
confidence: 92%
See 2 more Smart Citations
“…The inductance value at the initial time is about 94% of the normal inductance. This value is basically consistent with the 90% obtained in the literature [21]. When the excitation current is stabilized at the operating current, the inductance still keeps increasing with a lower growth rate than in the excited phase.…”
Section: Effect Of Excitation Speed On the Inductance Of Hts Coilsupporting
confidence: 92%
“…The inductive voltage is computed as the line integral of the magnetic vector potential variation with respect to time calculated by A-formulation [21], and the value of superconducting inductance can be calculated from the induced voltage:…”
Section: Calculation Of Superconducting Magnets Inductance Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 illustrates the entire process. Our study demonstrated that this approach can be ten times faster compared to the original approach (modeling individual turns) without compromising accuracy [45].…”
Section: Coupled Numerical Model Of the Hts Coilmentioning
confidence: 83%
“…Various existing publications have presented a method that combines the circuit, and the FEM model [46,47]. We also suggest a sequential simulation method, as shown in figure 2 Therefore, the effect of current distribution due to the radial current and the screening current on magnetic field distribution can be analyzed by this method, and it will be discussed in the next section.…”
Section: Analysis Method: a Sequential Simulation Model Consisting Of...mentioning
confidence: 99%